The Practice of Reciting Asmā` al-Ḥusnā in Weekly Ḥalaqa - Abdul Wachid Luthfi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
The practice of reciting asmā`ul-ḥusnā by certain groups is in most cases intended to be a form of afterlife-oriented worship. Seeing the practice more closely, as practiced by the customer of the Bank Wakaf Mikro this article argues that the practice indeed has in itself a formal-substantive part, that is the recitation of asmā`ul-ḥusnā. It also at the same time argues that the very practice serves as a means to generate social/cultural benefit for the performers. Furthermore, the practice observed in this research also finds its root on the prophetic hadith and thus a practice of living hadith. It shows that there has been a transmission and transformation of the hadith in both the text and content that results in, among others, the practice of reciting asmā`ul-ḥusnā by certain groups in a greatly varying ways